Upaya Peningkatan Pemahaman Tentang Pentingnya Gizi Seimbang Bagi Balita Di Praktek Mandiri Bidan Sary Rahayu, S.ST Tahun 2024 - Asri Fitri Yati (Jurnal Informasi Pengabdian Masyarakat, 2024)
Balanced nutrition is defined as a daily diet that contains nutrients in the same quantity and type as a person's body needs and takes into account the principles of varied diet, physical activity, food hygiene, and ideal body weight or good nutritional status (Nurjannah et al, 2023). The human body needs nutrients to produce energy in order to carry out daily activities in the form of physical activity. Humans need nutrients to produce energy, for the growth and development process, to replace damaged body tissue, as building blocks, regulatory substances, to prevent disease, and to meet the body's needs (Nurjannah et al., 2023).